(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Geotextile-reinforced soil walls are like similar to the common sandbag walls used for different construction applications. Geotextile-reinforced wallscan be built to large heights due to the geotextile’s higher strength and a simple mechanized building process. Construction work does not necessitate the use of skilled labour or advanced machinery. Since many of the materials are prefabricated, construction can be completed in a comparatively short period of time. This paper discusses about the main design factors required to considered during the reinforcement of soil walls using geotextile.